Synthesis and preliminary evaluation of a novel positron emission tomography (PET) ligand for imaging fatty acid amide hydrolase (FAAH). Issue 21 (1st November 2020) - Chen, Zhen; Hou, Lu; Gan, Jiefeng; Cai, Qijun; Ye, Weijian; Chen, Jiahui; Tan, Zhiqiang; Zheng, Chao; Li, Guocong; Xu, Hao; Fowler, Christopher J.; Liang, Steven H.; et al.
Graphical abstract: Abstract: Fatty acid amide hydrolase (FAAH) exerts its main function in the catabolism of the endogenous chemical messenger anandamide (AEA), thus modulating the endocannabinoid (eCB) pathway. Inhibition of FAAH may serve as an effective strategy to relieve anxiety and possibly other central nervous system (CNS)-related disorders. Positron emission tomography (PET) would facilitate us to better understand the relationship between FAAH in certain disease conditions, and accelerate clinical translation of FAAH inhibitors by providing in vivo quantitative information. So far, most PET tracers show irreversible binding patterns with FAAH, which would result in complicated quantitative processes. Herein, we have identified a new FAAH inhibitor (1-((1-methyl-1 H -indol-2-yl)methyl)piperidin-4-yl)(oxazol-2-yl)methanone (8 ) which inhibits the hydrolysis of AEA in the brain with high potency (IC50 value 11 nM at a substrate concentration of 0.5 µM), and without showing time-dependency. The PET tracer [ 11 C]8 (also called [ 11 C]FAAH-1906) was successfully radiolabeled with [ 11 C]MeI in 17 ± 6% decay-corrected radiochemical yield ( n  = 7) with >74.0 GBq/μmol (2 Ci/μmol) molar activity and >99% radiochemical purity. Ex vivo biodistribution and blocking studies of [ 11 C]8 in normal mice were also conducted, indicating good brain penetration, high brain target selectivity, and modest to excellent target selectivity in peripheral tissues. Thus, [ 11 C]8 is a potentially useful PET ligand with enzyme inhibitory and target binding properties consistent with a reversible mode of action.